Budaya Koloman Simbol Kekuatan Kekeluarga di Desa Buddagan 1 Kecamatan Larangan Luar Kabupaten Pamekasan - Ramadhanti, Alika; Sumadi, Conny Dian; Roziah (Lembaga Citra Pustaka, 2024)
Column traditions such as Kolom Terba'ng/Tahlilan Kolom Hadrah Sholawatan have sprung up in the Buddagan village community. Yasnan Pillar. Sabellasan Column Study Column. Friday Column Ustad Column. Kolbun (Monthly Column) Practice Sholawat Nariyah and Tahlilan. The Koloman tradition must certainly be preserved as part of the local wealth of the community, and its presence strengthened considering that the implication of its existence is to strengthen the faith and Islam of its citizens. The creation of a harmonious life between citizens, away from divisions, can improve morality and harmony between citizens who have been divided and threatened. Community empowerment to continue to develop, preserve their awareness and strengthen the pillars of their traditions requires the support of various existing elements to participate in the struggle to preserve the teachings of Islam Rahmatan Lir Al-Alamin which is the Islamic Value of the Community. This is because every column of activities is always filled with Islamic ritual teachings. Of course, in this case, a strengthened strategy is needed, including ongoing approaches and guidance, if necessary, becoming part of the column membership.